Facile Access to 1,5-Benzodiazepines via Amine-Promoted (4+3) Annulations of δ-Acetoxy Allenoates with o-Diaminobenzenes under Mild Conditions - Wang, Yi-Fan; He, Cheng-Yu; Hou, Longlei; Tian, Ping; Lin, Guo-Qiang; Tong, Xiaofeng (Synlett, 2018)
An amine-promoted (4+3) annulation of δ-acetoxy allenoate with o-diaminobenzene is reported, providing a facile access to 1,5-benzodiazepine. This method features wide reaction scope, mild conditions, and readily available starting materials. The cascade reaction involves aza-Michael addition of o-diaminobenzene to allenoate, elimination of acetate group, and subsequent 1,6-aza-Michael addition.
Keywords: 1,5-benzodiazepine; annulation; allenoate; diaminobenzene; catalyst-free